2012
DOI: 10.1002/srin.201200056
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Physical and Chemical Properties of Electric Arc Furnace Dusts for the Purposes of Their Utilization

Abstract: Electric arc furnace dusts are among the most environment polluting wastes. Numerous utilization technologies have been developed for dusts containing up to 4% of Zn and more than 20% of Zn. However, the remaining part of steelmaking dusts are the most problematic ones, as they are mostly dumped generating costs and posing serious environmental threats. This paper provides an analysis of the potential utilization options for dusts containing ca. 10% of zinc generated in a single electric steelmaking shop. Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 2 publications
0
2
1
1
Order By: Relevance
“…In previous studies, zinc was represented as the major element among all other elements in EFAD, with a value between 7 and 40 wt%. 2,23,24 However, in the present study, the amount of zinc is about 0.4 wt%, which is significantly lower compared with reported previous works.…”
Section: The Adsorbent Characterizationcontrasting
confidence: 90%
See 1 more Smart Citation
“…In previous studies, zinc was represented as the major element among all other elements in EFAD, with a value between 7 and 40 wt%. 2,23,24 However, in the present study, the amount of zinc is about 0.4 wt%, which is significantly lower compared with reported previous works.…”
Section: The Adsorbent Characterizationcontrasting
confidence: 90%
“…The chemical and physical properties of EFAD (Figure 2a) considered in this study is including (a) dimensions and shape of particles, (b) density: absolute, bulk, and tapped dust density, (c) grain composition, (d) dampness and hygroscopicity, (e) porosity of dust shell, (f) cone angle of heaped dust and angle of repose dust. 2,22 On the other hand, XRD patterns (Figure 2b) confirmed the presence of magmatic compounds in EAFD, and from the Mössbauer spectra, the material EFAD presents 18% of the iron phases of magnetite. 9,22 This characterization confirmed that EFAD potency is admissible for separating magnetic compounds for using as the magnetic adsorbent for water treatment.…”
mentioning
confidence: 84%
“…Atualmente, cerca de 70% do PAE é disposto em aterros industriais, devido à falta de tecnologias alternativas de baixo custo para sua reciclagem. 8 Uma alternativa que tem despertado interesse nos últimos anos é o processo de estabilização química, ou vitrificação, que consiste na produção de materiais cerâmicos para construção civil utilizando como matéria prima o pó de aciaria elétrica, 2,[8][9][10][11] e em reações Fenton heterogêneo para degradação de contaminantes orgânicos. 12 Devido ao alto teor de ferro no PAE, este pode ser um material interessante para aplicações em reações para remediação ambiental, como redução do Cr(VI) para Cr(III …”
Section: Introductionunclassified
“…Its disposal is costly and requires special secure landfills due to a possible elution of heavy metals and, thus, pollution of the environment [5,6]. Otherwise, utilization of the EAF dusts for production of ceramics, concrete, cement clinker, industrial glass [7][8][9] has gained attention recently.…”
Section: Introductionmentioning
confidence: 99%